Compliance Behavior Analysis of the Ship Crew to the International Safety Management (Ism) Code in Indonesia - Mamahit, Desi Albert; Daryanto, Heny K; Sumarwan, Ujang; Yusuf, Eva Zhoriva (International Journal of Management and Sustainability, 2013)
The purpose of this code is to provide international standards for the management and safe operation of ships and pollution prevention Furthermore, this study has the objective to identify the role of the ISM Code on maritime activities in Indonesia, knowing the perceptions and attitudes regarding the conduct of the crew boat ISM Code. Location research is conducted on the crew that was in the Port of Tanjung Priok in Jakarta. Data collection and processing is done for 3 months. The study was conducted using a survey approach by distributing questionnaires to the crew (respondents) from different hierarchy. Respondents were asked to fill out questionnaires about the intentions of the respondents in the implementation and compliance with the ISM Code safety rules for shipping. The primary data used in this study were obtained by a structured interview to the crew of passenger ships carrying commodities and goods in the country. Selection of boats done by purposive method, which is the selected ship types ship transporting passengers and goods in the domestic commodities. While the selection is done by the crew convenience method which is one form of non-random sampling methods or non-probabilistic unrestricted. The selection of the crew carried out when the ship was leaning / docked in the port of Tanjung Priok Jakarta and Merak port in Banten. Based on these results it can be concluded in general that the respondents are interested in the concept of the ISM Code as ineffectively to be more related to the supervision of the safety of shipping. It is turns out to be a featured subject of their compliance with the ISM Code as well as the application of this rule is also easy to understand. However, not all respondents are interested in the ISM Code, this is because the respondents consider that the ISM Code executed is just a formality and then it is not supported by the safety adequate equipment, non-compliance crew also based on the lack of socialization of the ISM Code.